Analysis Studies Appropriateness Transformation Of Higher Education At Universities : Studies STIE Ganesha Case - Fadli, Ahmad; Pardian, Ramadani; Fahri, Fahri; Saefullah, Aep; Tahang, Moh; Candra, Hendra; Ramayanti, Putri Noor (LPPM Universitas PGRI Sumatera Barat, 2025)
Study This aim For analyze appropriateness transformation at STIE Ganesha to Graha University Ganesha in frame increase quality education and services education tall to public . Study done for 1 year from January until December 2023 to 25 people consisting of from BPH YPGG, leaders , lecturers , employees and students of STIE Ganesa. The research was conducted using qualitative research methods with a single case study approach. Data was collected through interviews, literature studies and field observations. The research results show that consultation and assistance by the transformation team was very effective in strengthening the process of preparing the strategic plan for the transformation of Graha Ganesha University. The research results show that basic change form become University Graha Ganesha including a) saturation of study programs b) needs World Business And Industry (DUDI) in region South Tangerang city, c) Shape long PTS No or not enough responsive to need public. There are 5 foundations for the transformation of Graha Ganesha University, namely philosophical, sociological, psychological, historical and juridical foundations. The implementation of the education system adapts need provision means And infrastructure physique adequate is need Which very vital And main. Academic, administrative, financial and social aspects of community interest and development is an assessment of the feasibility of STIE Ganesha towards the transformation of Graha Ganesha University. This research makes a significant contribution to the development of higher education in Indonesia and is useful for stakeholders in formulating appropriate policies and strategies to improve the quality of higher education in Indonesia. The research has implications for formulating appropriate and contextual higher education transformation policies.